EWSR1-SMAD3-rearranged Fibroblastic Tumor: An Emerging Entity in an Increasingly More Complex Group of Fibroblastic/Myofibroblastic Neoplasms - Michal, Michael; Berry, Ryan S; Rubin, Brian P; Kilpatrick, Scott E; Agaimy, Abbas; Kazakov, Dmitry V; Steiner, Petr; Ptakova, Nikola; Martinek, Petr; Hadravsky, Ladislav; Michalova, Kvetoslava; Szep, Zoltan; et al. (The American journal of surgical pathology, 2018)
Three cases of superficial acral fibroblastic spindle cell neoplasms with EWSR1-SMAD3 fusion have been recently reported. Their differential diagnosis is broad, primarily comprising rare tumors from the fibroblastic/myofibroblastic category. The aim of this report is to present 4 new cases of this entity and to discuss the appropriate differential diagnosis. Also, as the ERG antibody seems to be a characteristic marker for these tumors, we analyzed ERG immunostaining characteristics in potential mimics of this entity. All cases in our cohort occurred in women aged 5 to 68 years (mean, 36.5 y). Two were located on the hand, 1 on foot, and the last case arose on the calf. The tumor size ranged from 1 to 1.5 cm in the greatest dimension, with a mean size of 1.2 cm. Except for one recent case, follow-up was available, ranging from 7 to 18 years (mean, 11.7 y), with a recurrence noted in 1 case after 10 years. All tumors were subcutaneous and showed 2 main components. One consisted of bland, spindled cells with elongated nuclei which were round when observed on the cross-section. These cells mostly grew in relatively hypercellular, well-organized, and intersecting fascicles. The second component was prominently hyalinized and paucicellular, but lacked calcifications. Both components showed either a distinct zonation pattern, or they were randomly intermingled with each other. In all 3 analyzable tumors, next-generation sequencing showed EWSR1-SMAD3 gene fusion in each case. By fluorescence in situ hybridization, one tested case also revealed unbalanced rearrangement of the EWSR1 gene. All 4 cases showed strong, diffuse nuclear expression of ERG, whereas none of the mimics stained with this antibody except for weak to moderate staining in calcifying aponeurotic fibromas (9/10 cases). Two tumors showed focal weak to moderate expression of SAT-B2. The 4 herein presented cases further broaden the clinicopathologic spectrum of tumors with EWSR1-SMAD3 gene fusion. They also confirm that they represent a novel entity for which we propose the name EWSR1-SMAD3-rearranged fibroblastic Tumor. Our study also proves that in the context of fibroblastic/myofibroblastic tumors, ERG immunohistochemistry is a relatively specific marker for these neoplasms.
Keywords: dospělí; Female; Phenotype; předškolní dítě; Adult; výsledek terapie; genová přestavba; ženské pohlaví; biopsie; High-Throughput Nucleotide Sequencing; Immunohistochemistry; lidé; fibroblasty asociované s nádorem; Gene Fusion; protein Smad3; genetická predispozice k nemoci; Treatment Outcome; Genetic Predisposition to Disease; nádory z pojivové a měkké tkáně; imunohistochemie; Smad3 Protein; retrospektivní studie; transkripční regulátor ERG; myofibroblasty; nádorové biomarkery; Aged; Biopsy; vysoce účinné nukleotidové sekvenování; Child, Preschool; Myofibroblasts; protein EWS vázající RNA; Gene Rearrangement; fúze genů; Biomarkers, Tumor; hybridizace in situ fluorescenční; Neoplasms, Connective and Soft Tissue; Cancer-Associated Fibroblasts; senioři; fenotyp; Transcriptional Regulator ERG; In Situ Hybridization, Fluorescence; Retrospective Studies; RNA-Binding Protein EWS; Humans